2020
DOI: 10.1177/0363546520925833
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the Latarjet Procedure Versus Free Bone Block Procedures for Anterior Shoulder Instability: A Systematic Review and Meta-analysis

Abstract: Background: Free bone block (FBB) procedures for anterior shoulder instability have been proposed as an alternative to or bail-out for the Latarjet procedure. However, studies comparing the outcomes of these treatment modalities are limited. Purpose: To systematically review and perform a meta-analysis comparing the clinical outcomes of patients undergoing anterior shoulder stabilization with a Latarjet or FBB procedure. Study Design: Systematic review and meta-analysis; Level of evidence, 4. Methods: PubMed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 113 publications
4
46
0
Order By: Relevance
“…Our results demonstrated similar outcomes at nearly 4-year follow-up as compared with historical male controls. 9,13 Notably, in this series, female patients with recurrent anterior instability experienced significant improvements in ASES, SST, and VAS scores. Only 1 patient in our cohort who underwent the Latarjet for glenoid bone augmentation experienced recurrent instability, for an overall recurrence rate of 5.9%, consistent with previously published rates of 1% to 8%.…”
Section: Discussionmentioning
confidence: 66%
“…Our results demonstrated similar outcomes at nearly 4-year follow-up as compared with historical male controls. 9,13 Notably, in this series, female patients with recurrent anterior instability experienced significant improvements in ASES, SST, and VAS scores. Only 1 patient in our cohort who underwent the Latarjet for glenoid bone augmentation experienced recurrent instability, for an overall recurrence rate of 5.9%, consistent with previously published rates of 1% to 8%.…”
Section: Discussionmentioning
confidence: 66%
“…Since 2014, at least 4 further studies 5-7,24 have compared outcomes between the arthroscopic Bankart and Latarjet procedures, suggesting that the difference between the 2 procedures concerning the quality of outcomes significantly increases with longer follow-up time. This has also been backed by a recent review 8 focusing on the long-term efficacy of Latarjet procedures alone. Considering these novel and important findings, the current article aims to provide an up-to-date review of the evidence, taking all known factors into account including the hitherto not systematically analyzed important aspect of follow-up time.…”
mentioning
confidence: 98%
“…One systematic review by Gilat et al demonstrated that bone grafting had a rate of recurrent instability (3%), osteoarthritis (12%), other complications (5%) a return to sports (88%) that was not significantly different to patients who underwent the Latarjet procedure; PRO data was also similar with both procedures demonstrating a significant improvement in American Shoulder and Elbow Surgeons score amongst other PROs. 105 Outcome data for bone grafting for posterior shoulder instability is less abundant but a study by Meuffels et al showed that at a median of 18 years, 6 of 11 patients were satisfied with their procedure and would elect to have the intervention again. 106 Seven of 11 had recurrent instability and 4 patients had a recurrent episode of dislocation.…”
Section: Anterior/posterior Bone Graftingmentioning
confidence: 99%
“…Complications after anterior or posterior glenoid bone grafting include hardware failure, painful hardware, osteoarthritis, 92 donor site pain (if autograft was harvested), 105 and specifically brachial plexus injury in anterior bone graft placement. 100 Kowalski et al demonstrated in a large Pearldiver database study that both anterior and posterior glenoid bone graft had an overall complication rate (dislocation, closed adhesion release, or reoperation) of approximately 20%, which was significantly greater than Bankart repair.…”
Section: Anterior/posterior Bone Graftingmentioning
confidence: 99%
See 1 more Smart Citation